South Korean counselors’ perceived multicultural counseling competence: Relationship with openness to experience, perceived general counseling competence, and multicultural counseling education/practice - Kim, Minjeong; Cho, Hwa Jin (Journal of Multicultural Counseling and Development, 2023)
This study investigated variables related to the perceived multicultural counseling competence (MCC) of South Korean counselors. The relationship between perceived MCC and demographic information was explored, and effects of openness to experience, general counseling competence, and multicultural counseling education/practice on perceived MCC were examined. Results revealed no relationship with demographic information and perceived MCC and significant effects of general counseling competence and multucultural counseling education/practice on perceived MCC. Implications for multicultural counseling training and future research are discussed.
Keywords: capacitación en asesoramiento multicultural; competencia en asesoramiento multicultural; consejeros surcoreanos; multicultural counseling competence; multicultural counseling training; South Korean counselors